New mono and bimetallic chloroquine derivatives : synthesis and evaluation as antiparasitic agents - Blackie, Margaret Anne Lillias (University of Cape Town, 2014)
Includes bibliographical references. === Several series of new ferrocenyl-quinoline antimalarial agents have been synthesised and fully characterised using standard spectroscopic and analytical techniques. The molecular structure of N-(7-Chloro-quinolin-4-yl)-N'-[2 -( N”,N""-dimethylaminomethyl)ferrocenylmethyl]-ethane-1.2-diamine has been determined by x-ray crystallography. N-(7-Chloro-quinolin-4-yl)-N'-[2-( N”, N""-dimethylaminomethyl)ferrocenylmethyl]-alkyl-1 ,n-diamine compounds were made where n = 2-6. These compounds contain a reactive secondary amine centre through which derivatisation to form aryl urea and aryl sulfonamide compounds was achieved. Complexes of the types: triphenylphosphine(L)gold(l) nitrate, pentafluorophenyl(L)gold(l) and chloro(cyclooctadiene)(L)rhodium(l) have been synthesised (where L = chloroquine, ferroquine, N-(7-chloro-quinolin-4-yl)-N'-[2-( N”, N""-dimethylaminomethyl)ferrocenyl methyl]-ethane-1 ,2-diamine, 3-benzyl-1-[2-(7-chloro-quinolin-4-ylamino)-ethyl]-1-[2-(N"",N""-dimethylaminomethyl)-ferrocenylmethyl]urea). All compounds have been evaluated against chloroquine sensitive and chloroquine resistant strains of Plasmodium falciparum. In most cases good activity was found in both strains of the parasite. N-(7-Chloro-quinol in-4-yl)-N'-[2 -( N”, N""-dimethylaminomethyl)ferrocenyl methyl]-alkyl-1, n-diamine compounds have been made where n = 2-6. It was found that in vitro efficacy against P. falciparum diminished with increasing spacer length. The introduction of the aryl urea moiety served to influence efficacy towards P. falciparum and toxicity towards mammalian cells. In some cases the toxicity was significantly reduced accompanied by an improvement in efficacy. The coordination complexes where L = chloroquine showed improved efficacy in the chloroquine resistant K1 strain of P. falciparum. In the heterobimetallic complexes, the ligand L showed equivalent or better in vitro efficacy than the coordination complexes of L against both chloroquine sensitive D10 and chloroquine resistant K1 strains of P. falciparum. Preliminary structure-activity studies were carried out on some of the prepared compounds. Phenylene analogues of some of the ferrocenyl compounds have been synthesized and it was found that the analogues show similar in vitro efficacy to each other in both chloroquine sensitive 3D7 and chloroquine resistant K1 strains of P. falciparum. The presence of a ferrocenyl moiety in the side chain of chloroquine analogues appears to have a synergistic or additive effect on in vitro efficacy.